Bhekalan dalam Tradisi dan Hukum (Studi Kasus pada Masyarakat Pakisan) - Muzayyanah (Al-Adillah: Jurnal Hukum Islam, 2021)
Proposals are not a condition of marriage. However, the prevailing practice in the community shows that the proposal is a preliminary step that is almost certainly done in the community. It is customary in Pakisan village, that to carry out a marriage, the Bhekalan process is preceded. Bhekalan in Indonesian is the same as engagement. Bhekalan bond occurs after the man proposes to the woman either by himself or through an intermediary, and the proposal is accepted by the woman. The period between the receipt of the application and the holding of the marriage is called the Bhekalan period. Bhekalan bond not only changes the status between a man and a woman as a married couple (engaged), but also changes the views and attitudes of parents and society. Parents will make allowances for the association of abhekalan couples, which previously were very strict on the association of their children. They are given the freedom to go alone, together, stay at Bhekalnya's house, especially during Eid and other events. It became a normal thing for them. Seeing the condition of the Pakisan people who incidentally have sufficient religious knowledge, both formal education, madrasah diniyah or Islamic boarding schools, the author feels the need to raise this issue into a scientific work by looking at the association during the Bhekalan period in Pakisan village from the point of view of Islamic law and customary law, Of course, it cannot be separated from today's social context. Therefore, it must refer to the principle of the levels that occur in society (social stratification).